2020
DOI: 10.1371/journal.pone.0233802
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the implementation of public-private partnerships in the healthcare sector in the Kingdom of Saudi Arabia

Abstract: Background Saudi Arabia is considering increasing the role of the private sector's participation in financing and delivering healthcare services through the adoption of Public-Private Partnerships (PPPs). However, the adoption and successful implementation of PPPs in the Saudi healthcare sector requires careful attention to overcome potential obstacles. Objectives This study investigates and identifies potential barriers to the successful implementation of PPPs in the Saudi healthcare sector. Methods A pre-tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 48 publications
1
22
0
7
Order By: Relevance
“…Kuruvila [ 11 ] argued that less-experienced NPOs struggle with their functioning and internal management of partnerships and need to build their management capacities to navigate their relationships with partners. These challenges in Saudi Arabia were related to a shortage of professionals qualified to handle cross-sector partnerships; a lack of expertise in establishing governance principles; a lack of co-ordination and networking skills with various actors; and the weakness of transparency and accountability measures [ 61 , 118 ]. In this context, Huyse, Phlix [ 119 ] concluded that less-experienced NPOs should invest in a clear vision of the nature of the capacities that they wish to build.…”
Section: Discussionmentioning
confidence: 99%
“…Kuruvila [ 11 ] argued that less-experienced NPOs struggle with their functioning and internal management of partnerships and need to build their management capacities to navigate their relationships with partners. These challenges in Saudi Arabia were related to a shortage of professionals qualified to handle cross-sector partnerships; a lack of expertise in establishing governance principles; a lack of co-ordination and networking skills with various actors; and the weakness of transparency and accountability measures [ 61 , 118 ]. In this context, Huyse, Phlix [ 119 ] concluded that less-experienced NPOs should invest in a clear vision of the nature of the capacities that they wish to build.…”
Section: Discussionmentioning
confidence: 99%
“…Tabel 1 menunjukkan terdapat enam variabel dengan 27 indikator yang tersebar disetiap variabelnya. Enam variabel tersebut yaitu: Social, Legal, Economic, Environment, Politic, Technology (SLEEPT) [12]. Variabel ekonomi terdiri dari tujuh indikator, variabel lingkungan terdiri dari empat indikator, variabel legal terdiri dari tiga indikator, variabel politik terdiri dari dua indikator, variabel sosial terdiri dari lima indikator, variabel teknologi terdiri dari enam indikator.…”
Section: Hasil Dan Pembahasanunclassified
“…Pendekatan dalam memperoleh variabel dan indikator mengunakan pendekatan SLEEPT yang dianggap telah menjadi suatu alat ukur yang terverifikasi dalam menyediakan ketajaman analisis dalam suatu lingkungan bisnis, metode tersebut memungkinkan pemangku kepentingan untuk membangun sistem yang lebih efektif dan efisien dalam menganalisa suatu skema KPBU [12]. 27 Kurangnya pengalaman stakeholder [5] [12] Setelah identifikasi variabel, tahapan selanjutnya adalah melakukan survei pendahuluan yang melibatkan pakar dari bidang transportasi.…”
Section: Hasil Dan Pembahasanunclassified
See 2 more Smart Citations